2019
DOI: 10.1590/1678-4499.20180146
|View full text |Cite
|
Sign up to set email alerts
|

Canonical correlation for morphoagronomic and bromatological traits in silage corn genotypes

Abstract: The aim of this study is to assess whether there is linear dependence between groups of morphoagronomic and bromatological traits in hybrid silage corn. Nineteen topcross hybrids and five checks were assessed in two different environments in Campos dos Goytacazes and Itaocara counties, Rio de Janeiro State, during the growing seasons 2013/2014. The study followed a randomized blocks design with four replicates. The phenotypic and canonical correlations between the groups of seven morphoagronomic and five broma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 22 publications
2
8
1
Order By: Relevance
“…Estimates of correlations between secondary traits and yield components, secondary traits and amino acids, secondary and bioactive traits, secondary and micronutrient traits, yield and amino acid components, yield and bioactive components, yield components and micronutrients, amino acids and bioactive, amino acids and micronutrients, bioactive and micronutrients, were explained in II, III, III, V, III, V, II, V, V and IV canonical pairs, respectively. Similar magnitude results were observed Alves, Cargnelutti-Filho, Burin and Toebe (2016), Nascimento et al (2008) and Crevelari et al (2019).…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…Estimates of correlations between secondary traits and yield components, secondary traits and amino acids, secondary and bioactive traits, secondary and micronutrient traits, yield and amino acid components, yield and bioactive components, yield components and micronutrients, amino acids and bioactive, amino acids and micronutrients, bioactive and micronutrients, were explained in II, III, III, V, III, V, II, V, V and IV canonical pairs, respectively. Similar magnitude results were observed Alves, Cargnelutti-Filho, Burin and Toebe (2016), Nascimento et al (2008) and Crevelari et al (2019).…”
Section: Resultssupporting
confidence: 86%
“…These estimates showed an inheritable association between characteristics. Therefore, they can be used in indirect selection processes in breeding programs (Crevelari et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results are consistent with a study of 18 corn hybrids during the 2003-2004 wetseason in southern Minas Gerais state in southeastern Brazil, which concluded that choosing hybrids with high digestibility is essential for the production of quality corn silage [40]. Unlike our results, evaluation of 19 corn hybrids for silage in Rio de Janeiro state in southeastern Brazil during the 2013 and 2014 dry seasons found that green matter yield can be used for indirect selection of bromatological quality [41]. Our 2020 dry-season average green matter yield (GMY) for corn silage (42.85 metric tons (t)/hectare (ha); Table 3) was 34.9% greater than average corn silage GMY (31.78 t/ha) in this same southeastern Brazil study, with our GMY having 25.8% lower standard deviation [41].…”
Section: Comparison To Previous Studiessupporting
confidence: 91%